Table of Content - - (Journal of engineering sciences and information technology, 2023)
Table of Content1. The impact of recruitment of materials to improve energy efficiency in buildingsCo-Prof. Rubaia Ali Bin Ali, Co-Prof. Fahd Saleh Gohar, Amr Rubaia Mukaydekh2. Space Recycle between Theory and practice - Case study: Ministries Square, Down TownEng. Maya Atef Bendary3. A Theoretical Comparative Review of Computer-Aided Landscape Design Tools: Features, Benefits, and LimitationsEng. Sami Abdullah Mandani, Eng. Abdullah Ebrahim Aljasem4. Analysis of the Lost Circulation process for the development of drilling operations  in Al-Omar oil field – SyriaEng. Tareq Ali Farid5. The Role of Artificial Intelligence in Civil Engineering Applications and ProgramsEng. Mohsen Saud Alghurair , Ayman Rushdy Fahim
Keywords: Journal of Engineering Sciences and Information Technology